Cutaneous tuberculosis: diagnosis, histopathology and treatment - Part II - Josemir Belo dos Santos; Ana Roberta Figueiredo; Cláudia Elise Ferraz; Márcia Helena de Oliveira; Perla Gomes da Silva; Vanessa Lucília Sileira de Medeiros (Sociedade Brasileira de Dermatologia, 2014)
The evolution in the knowledge of tuberculosis' physiopathology allowed not only a better understanding of the immunological factors involved in the disease process, but also the development of new laboratory tests, as well as the establishment of a histological classification that reflects the host's ability to contain the infectious agent. At the same time, the increasing bacilli resistance led to alterations in the basic tuberculosis treatment scheme in 2009. This article critically examines laboratory and histological investigations, treatment regimens for tuberculosis and possible adverse reactions to the most frequently used drugs.